Public Knowledge and Belief Regarding Antibiotic Use and Antimicrobial Resistance in Qatar - Hassan, Nesiya; Kunjavara, Jibin; Mannethodi, Kamaruddeen; Singh, Kalpana; Varghese, Annamma; Varughese, Bincymary; Thomas, Jeena Rajan; Salhab, Hamza Mohamad; Shah, Noor Bibi Khial Bad; Vinluan, Noreen Chua; et al. (National Journal of Community Medicine, 2022)
Background: Antibiotics act as a therapeutic weapon in eradicating pathogens. Antibiotics are the most common group of drugs misused for self-medication. This is a global public health concern and is one of the major contributing factors to antibiotic resistance (ABR). Objective: This study aimed to assess the knowledge and beliefs of the public in Qatar regarding appropriate antibiotic use and antimicrobial resistance. Methods: A cross-sectional research design was used to collect the information from the participants based on an adapted questionnaire from the Centers for Disease Control and Prevention (CDC) and the World Health Organization (WHO) between September – November 2018. The study enrolled 1000 participants who visited two large emergency departments (ED) of public hospitals in Qatar. Results: The mean knowledge and belief scores were 55.07±15.87 and 66.57±23.13 respectively. 42% of the participants had moderate knowledge regarding antibiotic and antimicrobial resistance. The majority of the participants (64.8%) believed that antibiotics fight against bacteria and viruses. The educational level significantly influences the belief of the participants. Graduates possess a higher belief score of 11.75±12.5 (P=0.001) compared to others. Conclusion: The key findings of this study highlighted the existing gap in knowledge among the public. A community-based health education program should be launched to raise citizen responsibility to use antibiotics judiciously.